THE FORMATION OF THE UZBEK LANGUAGE MANAGEMENT SYSTEM AND ITS DEVELOPMENT IN THE PERIOD OF ITS INDEPENDENCE (Scientific journal of the Fergana State University, 2025)
This article examines the formation of the Uzbek language office management system and its development after independence. The regulatory legal documents, manuals, and dictionaries governing the system have been analyzed. Problems in the field have been identified and examined, and proposals for their solutions have been presented.